Wirausaha Kreatif Pembuatan Masker Wajah dari Beras Bengkuang dan Daun Kelakai bagi Mahasiswa Fakultas Pertanian Universitas Palangka Raya: Creative Entrepreneur Making Face Masks from Jicama Rice and Kelakai Leaves for Students of the Faculty of Agriculture, Palangka Raya University - Nursiah, Nursiah; Maryani, Maryani; Norhayani, Norhayani; Rosita, Rosita; Rahayuningsih, Sri Endang Agustina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The problem-solving framework in this activity is to conduct training and guidance for students to foster an entrepreneurial culture. The selection of activities in the form of training is expected to develop entrepreneurial skills with the hope that when they have completed their studies they can develop and run their respective businesses. The purpose of this program is the implementation of training and mentoring for students to foster a student entrepreneurial culture within the Faculty of Agriculture, University of Palangka Raya, including: fostering and increasing the ability and interest of students to pursue entrepreneurship, increasing the creativity of student thinking in developing entrepreneurial skills, opening insights into the development of the entrepreneurial world in Central Kalimantan. The product manufacturing training that will be provided is the manufacture of face masks by utilizing natural ingredients for skin care using rice, bengkuang, and kelakai leaves. This activity is intended to make students more creative, and innovative in exploring natural resources in their environment to increase work productivity to later build a family economy independently. The results of the activity showed that the participants actively participated and understood the practices given. This activity can increase the knowledge and skills of partners and foster an entrepreneurial spirit in partners.